Rancang Bangun Sistem Informasi Pengendalian Pengadaan Material Proyek Berbasis Web Pada TJ Construction & Engineering - Luluk Fitriyah; Haryanto Tanuwijaya; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2015)
Material of construction is one of the limited resources in a construction project and also one of the main functions of construction activities whose value is between 25-40% can even reach 60% of the project budget. Therefore, material control process should be conducted in line with the implementation of the project. Control is done in order to keep the project running within the time limit, cost, and performance that specified in the plan. Good plan without accompanied with very good control may not produce a good output of the project in terms of cost, schedule and performance.To control the project material procurement, Procurement Division at TJ Construction & Engineering have difficulty to controlling material procurement planning in accordance with the conditions that exist in the project. In addition, procurement of material handling control system which is still to be checked one by one for each type of material raises new issues, namely the difficulty of determining the type and amount of material to be submitted to the procurement process as well as the difficulty of monitoring the status of the supply and use of the material during the implementation process the project.Material procurement control information system web-based project will be able to support the decision makers in TJ Construction & Engineering to address the problems that exist in the material procurement process. With more controlled material procurement, the goals and objectives of the final project has been set previously will be achieved as planned.